2019
DOI: 10.1186/s40792-019-0628-3
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic right common femoral artery occlusion caused by blunt bicycle handlebar injury: a case report

Abstract: Background Traumatic femoral artery occlusion caused by blunt impact to the groin is rare; this condition is called the “motor-scooter handlebar syndrome.” We herein report a case of traumatic femoral artery occlusion and performed a literature review on its diagnosis and treatment. Case presentation An 18-year-old man visited our hospital complaining of pain and swelling in his right groin and numbness in his right leg after a bicycle collision accident. Contrast compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
0
5
0
3
Order By: Relevance
“…Recently, Yoshimura et al 10 reported a similar case of blunt traumatic injury caused by the bicycle handlebar. The main differences between their case 10 and ours include the primary site of injury, worsening of the CT findings during conservative treatment, and the revascularization method (open surgery vs. endovascular stenting). As mentioned in their paper 10 , endovascular treatment was not performed because the primary site of injury was the common femoral artery, while it was the external iliac artery in our case.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Yoshimura et al 10 reported a similar case of blunt traumatic injury caused by the bicycle handlebar. The main differences between their case 10 and ours include the primary site of injury, worsening of the CT findings during conservative treatment, and the revascularization method (open surgery vs. endovascular stenting). As mentioned in their paper 10 , endovascular treatment was not performed because the primary site of injury was the common femoral artery, while it was the external iliac artery in our case.…”
Section: Discussionmentioning
confidence: 98%
“…It is very rare to see isolated femoral artery injury without any injury to the bone. In 1968, motor scooter handlebar syndrome was described where there is injury to the common femoral artery without pelvic or femoral fracture 4 . This syndrome was described as a result of compression of the artery by the inguinal ligament.…”
Section: Discussionmentioning
confidence: 99%
“…Frantzらは,外傷における下肢血管損傷の中で,総大腿動脈損傷の占める割合は約5.3%と報告している 1)。総大腿動脈損傷の受傷機転に関して,銃創や刺創を含む鋭的損傷の頻度が約80%と大半を占めるのに対して,鈍的損傷の頻度は約20%と少ない 1)。四肢の鋭的損傷では,血管の外膜から内膜へ至る全層の損傷が生じる一方で,鈍的損傷では内膜のみの局所的な損傷が起こりうる。本例のような鈍的損傷に伴う,CFAの内膜損傷の頻度は不詳であるが,我々が渉猟しえた限りでは,本例と同様に18歳以上の成人における,CFAの内膜損傷の既報は14例のみであり,比較的稀と推測される(Table 2) 2), 3), 4), 5), 6), 7), 8), 9), 10), 11), 12), 13), 14)。既報14例の平均年齢は29.5歳であり,若年者に多い傾向がみられた。受傷機転に関して,全例が鈍的損傷であり,うち9例で自転車またはバイクのハンドルが関与していた。全例片側性で,右7例,左7例と左右差は認められなかった。…”
Section: 考  察unclassified